2006
DOI: 10.1182/blood-2005-11-4659
|View full text |Cite
|
Sign up to set email alerts
|

Splenic marginal zone lymphoma: a prognostic model for clinical use

Abstract: The Integruppo Italiano Linfomi (IIL) carried out a study to assess the outcomes of splenic marginal zone lymphoma and to identify prognostic factors in 309 patients. The 5-year cause-specific survival (CSS) rate was 76%. In univariate analysis, the parameters predictive of shorter CSS were hemoglobin levels below 12 g/dL (P < .001), albumin levels below 3.5 g/dL (P ‫؍‬ .001), International Prognostic Index (IPI) scores of 2 to 3 (P < .001), lactate dehydrogenase (LDH) levels above normal (P < .001), age older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
172
4
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(197 citation statements)
references
References 26 publications
14
172
4
5
Order By: Relevance
“…In the small proportion of patients with concomitant HCV infection, interferon-a 2b (IFN), ribavirin or a combination of both these agents has demonstrated a significant activity with clearance of HCV RNA in the blood; 8,77,78 therefore, these agents should be considered in the therapeutic scenario as a first line in this small cohort of patients. A minority of patients (ca.…”
Section: Management Of Smzlmentioning
confidence: 99%
“…In the small proportion of patients with concomitant HCV infection, interferon-a 2b (IFN), ribavirin or a combination of both these agents has demonstrated a significant activity with clearance of HCV RNA in the blood; 8,77,78 therefore, these agents should be considered in the therapeutic scenario as a first line in this small cohort of patients. A minority of patients (ca.…”
Section: Management Of Smzlmentioning
confidence: 99%
“…A study by the Italian group in 309 patients suggested three parameters predictive for a shorter cause-specific survival: hemoglobin less than 12 g/dl, elevated LDH and albumin less than 35 g/dl. These authors proposed a clinical prognostic model considering three categories: low risk (no adverse factors), intermediate risk (one adverse factor) and high risk (two or three adverse factors) [31]. However, it must be considered that the group of patients included was heterogeneous, there was a lack of comprehensive information on other biological parameters and that these patients were probably managed differently in the various centers with regard to initiation of treatment and use of therapeutic approaches shown to be effective in this lymphoma.…”
Section: Which Clinical and Biological Factors Predict For Prognosis Inmentioning
confidence: 99%
“…The Italian Society of Haematology, the Italian Society of Experimental Haematology, and the Italian Bone Marrow Transplantation Group have published guidelines for the management of both follicular and non-follicular i-NHL patients [4,5], suggesting WW as a valuable initial option especially in asymptomatic patients with FL stage II-IV and low tumour burden [4]. Similar to FL, asymptomatic patients with splenic MZL are commonly monitored without any treatment since WW does not compromise survival [6]; nevertheless, patients should be treated if they are symptomatic or have bulky disease or cytopenia [7]. Some MALT lymphoma patients can be monitored with WW as well, without significantly modifying survival rates [8].…”
Section: Introductionmentioning
confidence: 99%